Synthesis and anti-OXPHOS, antitumor activities of DLC modified spinosyn derivatives. Issue 9 (1st May 2020) - Ma, Da-You; Lai, Qin; Peng, Kun-Jian; Wang, Long-Long; Li, Zeng-Xia; Liu, Li-Jun; Luo, Zhi-Yong; Liu, Su-You
Graphical abstract: Highlights: Twelve novel DLC (delocalized lipophilic cation) modified spinosyn derivatives were synthesized. Greatly enhanced antiproliferative activities towards human cancer cells. Lipophicility has a great influence on the antiproliferative effects of these derivatives. Both the isoquinolinium derivative 7b and triphenylphosphinium derivative 8b exhibited remarkably enhanced OXPHOS inhibition and apoptosis inducing ability. Both 7b and 8b exhibited a certain extent of in vivo antitumor effect. Abstract: A series of DLC (delocalized lipophilic cation) modified spinosyn derivatives were synthesized and evaluated for antitumor efficacies both in vitro and in vivo . Cancer cell based antiproliferative assays indicated that the more lipophilic derivatives had stronger inhibitory effects on the tested cancer cell lines. Compound 7b and 8b exhibited strong anti-OXPHOS and apoptosis inducing ability. Notable antitumor efficacies of 7b (5 mg/kg) and 8b (2.5 mg/kg) were observed in the in vivo tumor xenograft experiments, however, lethal toxicities were observed on higher dosages. Our findings indicated that DLC modification is a viable strategy to enhance the anti-OXPHOS and antitumor efficacies of spinosyn derivatives.